Medial arterial calcification and diabetic neuropathy. Issue 6320 (27th March 1982) - Edmonds, M E; Morrison, N; Laws, J W; Watkins, P J
Abstract : X-ray examinations of the feet, knees, and hands were performed on 20 diabetics with severe neuropathy and 20 diabetics with no evidence of neuropathy but with a similar mean age and duration of diabetes. All were under 53 years old with no clinical evidence of peripheral vascular disease. Medial arterial calcification was much more common and extensive in the patients with neuropathy, occurring in the feet in 15 and in the hands in eight compared with in four (p less than 0.001) and none (p less than 0.001) of the controls respectively. Although there was some correlation between calcification and both proteinuria (p less than 0.05) and proliferative retinopathy (p less than 0.02), the association between calcification and neuropathy (p less than 0.001) was much stronger. Neuropathy, with sympathetic denervation of the smooth muscle of the tunica media, may be important in the aetiology of medial arterial calcification.